Phytosterols and the Digestive System: A Review Study from Insights into Their Potential Health Benefits and Safety - Edyta Miszczuk; Andrzej Bajguz; Łukasz Kiraga; Kijan Crowley; Magdalena Chłopecka (MDPI AG, 2024)
Phytosterols are a large group of substances belonging to sterols-compounds naturally occurring in the tissues of plants, animals, and humans. The most well-known animal sterol is cholesterol. Among phytosterols, the most significant compounds are β-sitosterol, stigmasterol, and campesterol. At present, they are mainly employed in functional food products designed to counteract cardiovascular disorders by lowering levels of 'bad' cholesterol, which stands as their most extensively studied purpose. It is currently understood that phytosterols may also alleviate conditions associated with the gastrointestinal system. Their beneficial pharmacological properties in relation to gastrointestinal tract include anti-inflammatory and hepatoprotective activity. Also, the anti-cancer properties as well as the impact on the gut microbiome could be a very interesting area of research, which might potentially lead to the discovery of their new application. This article provides consolidated knowledge on a new potential use of phytosterols, namely the treatment or prevention of gastrointestinal diseases. The cited studies indicate high therapeutic efficacy in conditions such as peptic ulcer disease, IBD or liver failure caused by hepatotoxic xenobiotics, however, these are mainly in vitro or in vivo studies. Nevertheless, studies to date indicate their therapeutic potential as adjunctive treatments to conventional therapies, which often exhibit unsatisfactory efficacy or serious side effects. Unfortunately, at this point there is a lack of significant clinical study data to use phytosterols in clinical practice in this area.